Tear matrix metalloproteinases-9 and ocular surface parameters in diabetics: a cross-sectional study in Shenyang, China - Ling Yang; Wei He; Jiayan Chen; Guanghao Qin; Emmanuel Eric Pazo; Zhengpeng Qu (BMJ Open)
Background Overexpression of tear matrix metalloproteinases-9 (MMP-9) on the ocular surface tissues has been reported to result in ocular surface damage. MMP-9 levels in tears have been listed as one of many tools for confirming dry eye disease (DED).Objective This investigation aimed to compare MMP-9 levels and ocular surface parameters in diabetic patients with and without DED.Design A cross-sectional study.Setting He Eye Specialist Hospital, Shenyang, China.Participants This study recruited 144 right eyes of 144 diabetic patients between November and December of 2023, and 110 patients with similar propensity scores were included in the analyses.Main outcome measures Non-invasive breakup time (NITBUT), tear film lipid layer (TFLL), conjunctival hyperaemia (redness score (RS)), corneoconjunctival staining (CS), corneal sensitivity and Ocular Surface Disease Index (OSDI) questionnaire were evaluated. MMP-9 was measured using an immunochromatography assay.Results In total, 55 patients (55 eyes) were grouped as diabetic dry eye (DDE) and 55 patients (55 eyes) as diabetic non-dry eye (DNDE). The mean MMP-9 concentrations were higher in patients with DDE than DNDE (70.63±52.06 ng/mL vs 33.98±33.93 ng/mL; p<0.001). The optimal cut-off value of MMP-9 to predict DED in diabetic patients was>52.5 ng/mL, with 58.2% sensitivity and 78.2% specificity.Conclusions MMP-9 concentration was higher in patients with DDE than DNDE. The MMP-9 test is a potential diagnostic tool for DDE. It may help follow-up diabetic patients with DED and guide clinicians in deciding on anti-inflammatory treatments for these patients.